PENGELOLAAN KEUANGAN KELUARGA MENUJU KELUARGA HARMONIS BAGI GURU DI KAWASAN KARTASURA - Melia Kusuma; Yulfan Arif Nurohman; Rina Sari Qurniawati; Fuad Hasyim; Waluyo Waluyo (ABDI MAKARTI, 2023)
Harmonious family is everyone's dream. One of the keys to a harmonious family is be good at managing family finances. The problem faced during the COVID-19 pandemic is level of income declined, so we must be able to manage family finances wisely and don't get caught in consumptive debt. The purpose of service is to help improve the literacy in managing family finances. Members of this community service is Al Fath Kindergarten School committee consisting of teachers, employees, parents, and local residents. As for the results of community service, partners have the ability to manage family finances and prepare financial reports properly to be A harmonious family.